Participatory governance in the public provision of housing: The case of local housing boards (LHB) in the Philippines - Marife Magno-Ballesteros; Jenica A. Ancheta (Philippine Institute for Development Studies (PIDS), 2018)
This study examines the effectiveness of the Local Housing Board (LHB) as a platform for participatory governance in the delivery of public housing in an urban setting. It looks into the conduct and outcomes of participation in the LHB using the case study approach. The results show that participatory governance through the Local Housing Board is still evolving. Many cities that institutionalized their LHBs, have used the Board as a legal tool to carry out eviction and demolition. However, in cases when citizens' participation is effectively implemented as the case of the Quezon City Housing Board, the solutions can lead to more acceptable socialized housing arrangements for the community. It could be a slow process but violent confrontations can be avoided and the outcomes can be sustainable in the long run when communities claim ownership of their housing. While participatory governance may not apply in all cases, community driven solutions should still be given optimum emphasis. For the LHB to enable the process, the decision-making process within the Board has to be strengthened with greater representation of Peoples organization; community participation in the selection of their representatives to the Board; and transparency in discussion of issues and decisions of the Board. The LHB should be given funding and made the sole mechanism for consultation and public deliberation concerning public housing services. Its role can also be expanded to include that of a mobilizer for Peoples Plan enabling the implementation of community driven housing projects.
Keywords: 330; governance theory; participatory governance; peoples' participation; local housing board; housing